PENGARUH SISTEM AKUNTANSI MANAJEMEN TERHADAP MANAJEMEN KUALITAS PROSES PADA PT.TELKOMSEL DISTRIBUTION CENTER MANADO - Worotikan, Maria Natalia; Morasa, Jenny; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Management accounting systems need to be implemented in a company to provide a basis for making business decisions so that management can be better prepared to manage and carry out the control functions. The purpose of this study is to analyze the effect of management accounting systems on quality management processes at PT. Telkomsel Distribution Center. The type of this study is quantitative research. The location of this study is Telkomsel Distribution Center Manado which is in form of survey with distributing questionnaires that had been prepared previously to conduct research. The population and sample are all employees at the Telkomsel Distribution Center Manado with 40 respondents. Retrieval of data using saturated samples. Data analysis using simple regression with hypothesis testing. The results of the study are on relationship model between management accounting systems and process quality management. There is a positive and significant relationship of management accounting systems to the management of process quality. The suggestion is that in an effort to improve management of process quality, management should improve management accounting systems of the company. The higher management accounting system the better it improve process quality management of Manado Telkomsel Distribution Center.